Dengue virus infects the mouse eye following systemic or intracranial infection and induces inflammatory responses. (27th November 2019) - Norbury, Aidan J.; Calvert, Julie K.; Al-Shujairi, Wisam H.; Cabezas-Falcon, Sheila; Tang, Victoria; Ong, Li Ching; Alonso, Sylvie L.; Smith, Justine R.; Carr, Jillian M.
Abstract : Dengue virus (DENV) infection is associated with clinical ocular presentations and here DENV infection of the eye was assessed in mice. In an AG129 mouse model of antibody-dependent enhancement of DENV infection, DENV RNA was detected in the eye and vascular changes were present in the retinae. Intraocular CD8 and IFN-γ mRNA were increased in mice born to DENV-naïve, but not DENV-immune mothers, while TNF-α mRNA was induced and significantly higher in mice born to DENV-immune than DENV-naïve mothers. DENV RNA was detected in the eye following intracranial DENV infection and CD8 mRNA but not IFN-γ nor TNF-α were induced. In all models, viperin was increased following DENV infection. Thus, DENV in the circulation or the brain can infect the eye and stimulate innate immune responses, with induction of viperin as one response that consistently occurs in multiple DENV eye-infection models in both an IFN-dependent and independent manner.